Characterisation of micropores in plasma deposited SiO x films by means of positron annihilation lifetime spectroscopy - Hoppe, C; Mitschker, F; Butterling, M; Liedke, M O; de los Arcos de Pedro, Maria Teresa; Awakowicz, P; Wagner, A; Grundmeier, Guido (Journal of Physics D: Applied Physics)

Influence of dielectric barrier plasma treatment of ZnMgAl alloy‐coated steel on the adsorption of organophosphonic acid monolayers - Knust, Steffen; Kuhlmann, Andreas; Orive, Alejandro G.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Surface and Interface Analysis)

Marktmissbrauch in digitalen Märkten - eine wettbewerbspolitische Analyse mit Fallbeispielen von Google, Facebook und Amazon - Niggemeyer, Laura

Challenges for Competition Policy in Data-Driven Mergers - Schlegel, Manuela

Marktmissbrauch in digitalen Märkten - Eine wettbewerbspolitische Analyse am Beispiel von Facebook - Neibert, Katharina

Zu den volkswirtschaftlichen Auswirkungen von Marktmacht am Fallbeispiel der Walt Disney Company - Naseri, Gitti

Preisdifferenzierung im Online-Handel am Beispiel Amazon und Obi - Laudage, Felix

Zuordnung und Anreizkompatibilität - Eine experimentelle Untersuchung - Posmetni, Lena

Auswirkungen der Preisdiskriminierung im Online Handel - Eine Wohlfahrtsanalyse am Beispiel von Amazon - Hensel, Jason

Zur Effizienzsteigerung durch Reputationsmechanismen auf digitalen Märkten - Multani, Manjinder Singh

Electrically controlled rapid adiabatic passage in a single quantum dot - Mukherjee, Amlan; Widhalm, Alex; Siebert, Dustin; Krehs, Sebastian; Sharma, Nandlal; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
Keywords: tet_topic_qd

Mean-field and full-field homogenization with polymorphic uncertain geometry and material parameters - Caylak, Ismail; Penner, Eduard; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)

Was bedeutet Ehre? Diskursethische Überlegungen zu den BBC-Reden Thomas Manns - Markewitz, Friedrich; Schuster, Britt-Marie; Wilk, Nicole M. (Diskursethisch)

Mensch, Maschine! Ein unplugged-Einstieg in KI und maschinelles Lernen. - Opel, Simone; Nordemann, Lina; Schulte, Carsten; Tenberge, Claudia (Merz Medien + Erziehung. Zeitschrift für Medienpädagogik.)

Organic Light‐Emitting Diodes Based on a Columnar Liquid‐Crystalline Perylene Emitter - Keum, Changmin; Becker, David; Archer, Emily; Bock, Harald; Kitzerow, Heinz-Siegfried; Gather, Malte C.; Murawski, Caroline (Advanced Optical Materials)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Dynamics of a liquid crystal-based modulator with germanium substrates for mid-infrared radiation - Risse, Anna Margareta; Schmidtke, Jürgen; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Einstellungen von Kindern gegenüber Schülerinnen und Schülern mit einem sonderpädagogischen Förderbedarf im Zusammenhang mit dem Vorbildverhalten ihrer Eltern. Vortrag auf der 8. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung gestalten – Partizipation erreichen – Digitalisierung nutzen“ - Löper, Marwin Felix; Hellmich, Frank; Hoya, Fabian Karl

Pre-service teachers’ cooperation and children’s social participation in inclusive primary schools. Single Paper. EARLI SIG 15 Biennial Conference 2020 `Special Educational Needs´. “Learning difficulties and inclusion: Challenges (and solutions) for the future” - Hoya, Fabian Karl; Schulze, Jan Roland; Hellmich, Frank; Schwab, Susanne; Blumberg, Eva

Familie und verantwortete Elternschaft - Landhäußer, Sandra (Handbuch Familie. Bildung, Erziehung und pädagogische Arbeitsfelder)
Das Handbuch Familie repräsentiert den theoretischen und empirischen Stand der Familienforschung aus konsequent interdisziplinärer Sicht. Mit dem Schwerpunkt auf die Themen Bildung und Erziehung und dem Bereich, der Familienarbeit in sozialpädagogischen Arbeitsfeldern bedeutet, bietet der Band die komplette Bandbreite Diskurses ab. In der neu konzipierten Struktur wird ein umfassendes Bild von Familie als einer pädagogischen Institution gezeichnet, in das die aktuellen wissenschaftlichen Erkenntnisse und Forschungsergebnisse einfließen.
Keywords: ng Armut Familientherapie Rechtsextreme Familen

Ambivalenzen der Förderung. Erziehungs- und Lernbegleitung für Kinder, Jugendliche und junge Erwachsene durch studentische Mentorinnen und Mentoren - Beerheide, N.; Dopheide, F.; Freitag, Christine; Koch, L.; Struchholz, C.; Westphal, Petra (Emotionale und soziale Entwicklung in der Pädagogik der Erziehungshilfe und bei Verhaltensstörungen)

Das Theater der Zärtlichkeit. Affektkultur und Inszenierungsstrategien in Tragödie und Komödie des vorbürgerlichen Zeitalters

Organische Chemie - Andexer, Jennifer N.; Beifuss, Uwe; Beuerle, Florian; Brasholz, Malte; Breinbauer, Rolf; Ernst, Martin; Greb, Julian; Gulder, Tobias; Hüttel, Wolfgang; Kath‐Schorr, Stephanie; Kordes, Markus; Lehmann, Matthias; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Erbium-Catalyzed Regioselective Isomerization–Cobalt-Catalyzed Transfer Hydrogenation Sequence for the Synthesis of Anti-Markovnikov Alcohols from Epoxides under Mild Conditions - Liu, Xin; Longwitz, Lars; Spiegelberg, Brian; Tönjes, Jan; Beweries, Torsten; Werner, Thomas (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Benzoxepinones: A new isoform-selective class of tumor associated carbonic anhydrase inhibitors - Grandane, Aiga; Nocentini, Alessio; Werner, Thomas; Zalubovskis, Raivis; Supuran, Claudiu T. (Bioorganic and Medicinal Chemistry)
Keywords: Organic Chemistry; Clinical Biochemistry; Drug Discovery; Pharmaceutical Science; Molecular Biology; Molecular Medicine; Biochemistry

Plasma‐Assisted Immobilization of a Phosphonium Salt and Its Use as a Catalyst in the Valorization of CO 2 - Hu, Yuya; Peglow, Sandra; Longwitz, Lars; Frank, Marcus; Epping, Jan Dirk; Brüser, Volker; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Stereoselective Synthesis of a cis-Cedrane-8,9-diol as a Key Intermediate for an Amber Odorant - Stefanow, Vivian; Grandane, Aiga; Eh, Marcus; Panten, Johannes; Spannenberg, Anke; Werner, Thomas (Organic Process Research and Development)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Selective Construction of C−C and C=C Bonds by Manganese Catalyzed Coupling of Alcohols with Phosphorus Ylides - Liu, Xin; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: General Chemistry

Catalytic, Kinetic, and Mechanistic Insights into the Fixation of CO2 with Epoxides Catalyzed by Phenol‐Functionalized Phosphonium Salts - Hu, Yuya; Wei, Zhihong; Frey, Anna; Kubis, Christoph; Ren, Chang‐Yue; Spannenberg, Anke; Jiao, Haijun; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Information asymmetry and the SEC framework in digital markets - On the role of reputation systems in alleviating buyers' skepticism and inducing their willingness to pay - Bellouchi, Houda

Standort, Perspektive und Haltung: Überlegungen zum Proprium der Kirchengeschichte als einer Disziplin theologischer Wissenschaft - Schmidt, Jochen (Kirchengeschichte)
Keywords: Kirchengeschichte; Theologie

FLP-catalysis meets hydrogen-bond activation - Sitte, Nikolai A.; Köring, Laura; Roesky, Peter W.; Paradies, Jan (Organic & Biomolecular Chemistry)
The potential of two chiral amidines and three non-chiral boranes in the metal-free hydrogen activation was explored.

Dually Crosslinked Supramolecular Hydrogel for Cancer Biomarker Sensing - Li, Jie; Ji, Chendong; Lü, Baozhong; Rodin, Maksim; Paradies, Jan; Yin, Meizhen; Kuckling, Dirk (ACS Applied Materials & Interfaces)

Palladium‐Catalyzed Polycondensation for the Synthesis of Poly(Aryl)Sulfides - Hou, Peng; Oechsle, Peter; Kuckling, Dirk; Paradies, Jan (Macromolecular Rapid Communications)

“Depression is the loneliest fucking thing on Earth” (Elisabeth Wurtzel): Depression memoirs as acts of lamentation? - Schmidt, Jochen (Erzähltes Selbst. Narrative Ethik aus theologischer und literaturwissenschaftlicher Perspektive – The narrated self. Narrative Ethics from the perspectives of theology and literary studies)

Erzähltes Selbst. Narrative Ethik aus theologischer und literaturwissenschaftlicher Perspektive – The narrated self. Narrative Ethics from the perspectives of theology and literary studies - Schmidt, Jochen

Die ethische Pascaline: Versuch über hermeneutische Ethik - Schmidt, Jochen (NZSTh)
Keywords: hermeneuthik; Ethik

Differences in event-related potentials indicate differential use of mental rotation processes in parity judgements of humanoid and alphanumeric stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias

Neuronale Korrelate der mentalen Rotation von menschlichen Figuren und alphanumerischen Stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias

Physical activity and health promotion for nursing staff in elderly care: a study protocol for a randomised controlled trial - Otto, Ann-Kathrin; Pietschmann, Juliane; Appelles, Luisa-Marie; Bebenek, Michael; Bischoff, Laura L; Hildebrand, Claudia; Johnen, Bettina; Jöllenbeck, Thomas; Kemmler, Wolfgang; Klotzbier, Thomas; Korbus, Heide; Rudisch, Julian; et al. (BMJ Open)
Introduction Nursing staff is burdened by high workload and stress. Furthermore, heavy lifting, as well as transferring nursing home residents, cause lumbar tissue damage and back pain. Exercise intervention studies to reduce work-related problems are rare and the evidence for efficacy of studies among nurses is limited. Studies including targeted analysis of requirements are necessary to generate effective recommendations and tailored interventions for health promotion programmes. The purpose of this multicentred intervention study is to identify work-related problems, to implement health promotion programmes and to evaluate their effectiveness. Methods and analysis A randomised controlled trial will be conducted, including a total of 48 nursing home facilities in eight regions of Germany with an estimated sample size of 700 nurses. Standardised ergonomics and posture training (10 weeks, once a week for 20–30 min) and subsequently, back-fitness training (12 weeks, once a week for 45–60 min) will be administered. Following the implementation of standardised health promotion programmes, further demand-oriented interventions can be implemented. The perceived exposure to work-related demands, work-related pain in different parts of the body, health-related quality of life, perceived stress, work-related patterns of behaviour and experience, presentism behaviour, work environment as well as general needs and barriers to health promotion, will be assessed at baseline (pre-test), at 10 weeks (post-test, after ergonomics training), at 22 weeks (post-test, after back-fitness training) and at 34 weeks of the programme (follow-up). Ethics and dissemination The study was reviewed and approved by the local ethics committee of the University of Hamburg (AZ: 2018_168). The results of the study will be published in open-access and international journals. Furthermore, the results will be presented in the participating nursing homes and at national and international conferences. Trial registration number DRKS.de (DRKS00015241).
Keywords: General Medicine

Schmerz und die Grenzen der Sprache - Schmidt, Jochen (Wege zum Menschen)

Mental rotation and performance in basketball: effects of self-controlled and externally controlled time constraints on the processing and execution of tactic board instructions with varied orientations - Krause, Daniel; Weigelt, Matthias (German Journal of Exercise and Sport Research)
Abstract Purpose In sports games, tactical instructions are mostly presented on tactic boards under temporal constraints determined by the length of time outs (e.g., 20–60 s time outs in basketball) and coaches’ instructional behavior. Thus, instructions should be presented in a way that enables fast and errorless information processing. High affordances in visual–spatial transformation (e.g., mental rotation processes) might both impede information processing and decrease execution performance. The aim of this study was to scrutinize the effect of different orientations of visual tactical displays on observation time under self-paced conditions as well as to compare the effects on execution performance to those of externally paced conditions. According to the self-determination theory, self-control over observation time is assumed to increase performance. Methods In a mixed-factors design with two factors, 48 participants were instructed to execute a basketball playing pattern, which was presented on a virtual tactic board in one of five different spatial disparities to the players’ on-court perspective. The Self-Paced Group determined the observation time in a self-controlled manner, whereas in the Yoked Group observation times were externally controlled, i.e., the observation time was constrained to match that of the Self-Paced Group.. Results The self-controlled time for watching the pattern before execution was significantly shorter and spatial accuracy in pattern execution was significantly higher for low disparity between instruction perspective and on-court perspective. Self-control over observation time did not affect execution accuracy. Conclusion The orientation effects might be explained by interfering mental rotation processes that are necessary to transform the instructional perspective into the players’ egocentric perspective. According to these results, coaches should align their tactic boards to their players’ on-court viewing perspective.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing - Budde, Kirsten; Barela, José Angelo; Figueiredo, Gabriella Andreeta; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: A detail of previous studies on mental rotation, which has not received any attention so far, relates to the testing situation of the participants. In nearly every study, participants were tested in a sitting posture (and not standing). However, when considering embodied cognition approaches on mental processes, participants may not be able to fully exploit these processes when performing mental rotation tasks in a sitting posture.
AIM: Therefore, the aim of the present study is to examine the potential influence of two different postures (sitting vs. standing), when solving mental body rotation tasks.
METHOD: Sixteen participants (6 females) were tested in two mental body-rotation tasks (MBRT), requiring either an object-based spatial transformation (based on a same-different judgment) or an egocentric transformation (based on a left-right judgment) in a sitting and in a standing posture. Reaction times and response errors were analysed in two three-way ANOVAs, with the factors orientation, task, and posture.
RESULTS: Results revealed an effect of orientation and task, indicating that participants performed better for egocentric than for object-based transformations. However, there was no effect of posture.
CONCLUSION: The different dynamics of postural control during sitting and standing do not induce different embodiment effects on mental rotation.
Keywords: General Engineering

The role of different directions of attention on the extent of implicit perception in soccer penalty kicking - Memmert, Daniel; Noël, Benjamin; Machlitt, Daniel; van der Kamp, John; Weigelt, Matthias (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

The Mental Rotation Ability of Expert Basketball Players: Identifying On-Court Plays - Weigelt, Matthias; Memmert, Daniel (Research Quarterly for Exercise and Sport)
Keywords: Nephrology; Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Der Tod und das Ding. Textilien und Vergänglichkeiten

DNA Origami Nano-Sheets and Nano-Rods Alter the Orientational Order in a Lyotropic Chromonic Liquid Crystal - Zhang, Bingru; Martens, Kevin; Kneer, Luisa; Funck, Timon; Nguyen, Linh; Berger, Ricarda; Dass, Mihir; Kempter, Susanne; Schmidtke, Jürgen; Liedl, Tim; Kitzerow, Heinz-Siegfried (Nanomaterials)
Rod-like and sheet-like nano-particles made of desoxyribonucleic acid (DNA) fabricated by the DNA origami method (base sequence-controlled self-organized folding of DNA) are dispersed in a lyotropic chromonic liquid crystal made of an aqueous solution of disodium cromoglycate. The respective liquid crystalline nanodispersions are doped with a dichroic fluorescent dye and their orientational order parameter is studied by means of polarized fluorescence spectroscopy. The presence of the nano-particles is found to slightly reduce the orientational order parameter of the nematic mesophase. Nano-rods with a large length/width ratio tend to preserve the orientational order, while more compact stiff nano-rods and especially nano-sheets reduce the order parameter to a larger extent. In spite of the difference between the sizes of the DNA nano-particles and the rod-like columnar aggregates forming the liquid crystal, a similarity between the shapes of the former and the latter seems to be better compatible with the orientational order of the liquid crystal.
Keywords: General Materials Science; General Chemical Engineering

Riesz distributions and Laplace transform in the Dunkl setting of type A - Rösler, Margit (Journal of Functional Analysis)
Keywords: Analysis

A METHODICAL APPROACH TO INTEGRATED PRODUCT DEVELOPMENT IN TOTAL HIP ARTHROPLASTY - Ley, P.-P.; Wirths, L.; Oleff, Christian; Jungreitmayr, F.; Vajna, S.; Paetzold, K.; Borg, J. C. (Proceedings of the Design Society: DESIGN Conference)
Abstract Hip joint arthroplasty is considered to be a safe, successful and cost-effective procedure to restore hip joint functionality. However, a successful hip joint arthroplasty affects different stakeholders e.g. patient and surgeon and depends on various influencing factors within the product life cycle as well as the applied technological opportunities. Due to the complex dependencies between influencing factors, technological opportunities and stakeholders, this contribution introduces an IPD-based approach to improve the quality of total hip arthroplasties.

Kinderladen - Göddertz, Nina (socialnet Lexikon)
Keywords: Erziehungswissenschaft; Sozialwissenschaft; Kinder

Ultrafast electric control of a single QD exciton - Förstner, Jens; Widhalm, A.; Mukherjee, A.; Krehs, S.; Jonas, B.; Spychala, K.; Förstner, Jens; Thiede, Andreas; Reuter, Dirk; Zrenner, Artur (11th International Conference on Quantum Dots)

PMD-Tolerant 20 krad/s Endless Polarization and Phase Control for BB84-Based QKD with TDM Pilot Signals - Koch, Benjamin; Noé, Reinhold (Photonic Networks; 21th ITG-Symposium)

Comparison of Optical Polarization-Dependent Loss Measurement Methods - Noé, Reinhold; Koch, Benjamin (Photonic Networks; 21th ITG-Symposium)

Who cooperates better with whom? – Effects of pre-service teachers’ collaboration on children’s social participation in primary school science lessons. Oral Paper Presentation, Symposium: “Inclusive Teaching Practices – A Way to Reach Every Student?” (Katharina-Theresa Lindner). ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Schwab, Susanne; Blumberg, Eva

Persönliche Ressourcen von Grundschullehrkräften im Zusammenhang mit ihrem Umgang mit heterogenen Lerngruppen im inklusiven Unterricht. Vortrag im Rahmen des Symposiums „Individualisierung des Lernens im inklusiven Unterricht aus der Perspektive von Lehrkräften und Kindern“ (Frank Hellmich & Susanne Schwab) auf der 8. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung gestalten – Partizipation erreichen – Digitalisierung nutzen“ - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Prädiktoren für Intentionen von Lehrkräften an inklusiven und nicht-inklusiven Schulen in Hinblick auf die Gestaltung individueller Lernprozesse. Vortrag auf der 8. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung gestalten – Partizipation erreichen – Digitalisierung nutzen“ - Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

Predictors of primary school students’ attitudes towards peers with special educational needs in their social-emotional development. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Löper, Marwin Felix; Hellmich, Frank

Individualisierung des Lernens im inklusiven Unterricht aus der Perspektive von Lehrkräften und Kindern. Symposium auf der 8. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung gestalten – Partizipation erreichen – Digitalisierung nutzen“ - Hellmich, Frank; Schwab, Susanne

Social participation in inclusive primary education – The importance of primary school students’ contact experiences for their attitudes towards peers with special educational needs. Oral Paper Presentation, Symposium: “Social Participation of Children with Special Education Needs: Acceptance, Attitudes, Friendships and Interventions” (Sílvia Alves, Manuela Sanches-Ferreira & Mónica Silveira-Maia). ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Löper, Marwin Felix; Görel, Gamze; Schwab, Susanne; Hellmich, Frank

The role of primary school teachers’ attitudes and self-efficacy beliefs for their intentions to deal with heterogeneity in (non-)inclusive education. Single Paper. ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

What are the requirements for a successful realisation of inclusion from primary school principals’ point of view? Single Paper. ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Görel, Gamze; Hellmich, Frank

How can primary school teachers’ self-efficacy beliefs in inclusive education be explained? Single Paper. ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Franzen, Katja; Hellmich, Frank

The role of contact experiences for primary school children’s attitudes towards peers with special educational needs. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Löper, Marwin Felix; Hellmich, Frank; Trauntschnig, Mike; Schwab, Susanne

Effects of primary school teachers’ self-efficacy beliefs and their attitudes on their everyday day practices in inclusive education. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

Determinants for primary school students’ attitudes towards peers with special educational needs in their social and emotional development. Single Paper. ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Löper, Marwin Felix; Hellmich, Frank

Effects of parental feedback on children’s reading motivation and their reading comprehension. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Hoya, Fabian Karl; Hellmich, Frank

Discussion on the panel “Inclusion: Perceptions, attitudes and relationships” (Moderator: Christoph Müller, Discussants: Anita Bexkens, Frank Hellmich & Timo Lüke). EARLI SIG 15 Biennial Conference 2020 `Special Educational Needs´. “Learning difficulties and inclusion: Challenges (and solutions) for the future” - Hellmich, Frank

Predictors for teachers’ intentions to deal with heterogeneity in (non-)inclusive primary schools. Single Paper. EARLI SIG 15 Biennial Conference 2020 `Special Educational Needs´. “Learning difficulties and inclusion: Challenges (and solutions) for the future” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Children’s contact experiences and their attitudes towards peers with special educational needs. Single Paper. EARLI SIG 15 Biennial Conference 2020 `Special Educational Needs´. “Learning difficulties and inclusion: Challenges (and solutions) for the future” - Hellmich, Frank; Löper, Marwin Felix; Schwab, Susanne

Primary school principals’ perspective on requirements for the implementation of inclusive education. Single Paper. EARLI SIG 15 Biennial Conference 2020 `Special Educational Needs´. “Learning difficulties and inclusion: Challenges (and solutions) for the future” - Görel, Gamze; Hellmich, Frank

Determinants of children’s attitudes towards peers with special educational needs. Single Paper. EARLI SIG 15 Biennial Conference 2020 `Special Educational Needs´. “Learning difficulties and inclusion: Challenges (and solutions) for the future” - Löper, Marwin Felix; Hellmich, Frank

Predictors of primary school teachers’ self-efficacy for inclusive education. Poster Presentation. EARLI SIG 15 Biennial Conference 2020 `Special Educational Needs´. “Learning difficulties and inclusion: Challenges (and solutions) for the future” - Franzen, Katja; Hellmich, Frank

Digitalisierung - Revolution des Lernens? - Herzig, Bardo (Mobile Medien im Schulkontext, Medienbildung und Gesellschaft)

Analytical Competence of Teachers – Assessing the Construct Validity by Means of Mixed Methods and Drawing Consequences for Teacher Education. - Plöger, Wilfried; Krepf, Matthias; Scholl, Daniel; Seifert, Andreas (Teacher Education Quaterly)

Editorial: Orientierungen in der digitalen Welt - Herzig, Bardo; Klar, T.-M.; Martin, A.; Meister, D. M. (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)

Einsatz digitaler Medien im Sachunterricht: Vorreiter Schweden!? - Blumberg, Eva; Sicking, Annika (Mobile Medien im Schulkontext, Medienbildung und Gesellschaft)

Ziele festlegen und formulieren - Blumberg, Eva (Sachunterricht begründet planen. Das Prozessmodell Generativer Unterrichtsplanung Sachunterricht (GUS) und seine Grundlagen)

Effects of pre-service teachers’ collaborative planning lessons on their professional self-concepts. Single Paper. ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Schulze, Jan Roland; Hoya, Fabian Karl; Blumberg, Eva; Hellmich, Frank

C 2 N: A Class of Covalent Frameworks with Unique Properties - Tian, Zhihong; Lopez Salas, Nieves; Liu, Chuntai; Liu, Tianxi; Antonietti, Markus (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Guanine‐Derived Porous Carbonaceous Materials: Towards C 1 N 1 - Kossmann, Janina; Heil, Tobias; Antonietti, Markus; Lopez Salas, Nieves (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Guanine condensates as covalent materials and the concept of cryptopores - Kossmann, Janina; Piankova, Diana; Tarakina, Nadezda V.; Heske, Julian; Kühne, Thomas D.; Schmidt, Johannes; Antonietti, Markus; Lopez Salas, Nieves (Carbon)
Keywords: General Chemistry; General Materials Science

Rediscovering Forgotten Members of the Graphene Family - Lopez Salas, Nieves; Kossmann, Janina; Antonietti, Markus (Accounts of Materials Research)

Professionelle Kompetenzwahrnehmung von Lehramtsstudierenden in Praxisphasen. Zusammenstellung eines Erhebungsinstruments mit den Schwerpunkten auf diagnostischen und didaktischen Kompetenzen sowie dem Umgang mit Heterogenität - Pieper, Catania; Kottmann, Brigitte; Miller, Susanne (HLZ - Herausforderung Lehrer_innenbildung, Zeitschrift zur Konzeption, Gestaltung und Diskussion)
Ausgehend von einem Forschungsvorhaben, welches sich für die Wahrnehmung und Entwicklung von professionellen Kompetenzen von Bachelorstudierenden während einer Praxisphase interessiert, wurde ein Erhebungsinstrument zusammengestellt, das sich am kompetenztheoretischen Professionsverständnis nach Baumert & Kunter (2006) orientiert. Weil die zu untersuchende Praxisphase am Standort Bielefeld bildungswissenschaftlich verankert ist und eine Konkretisierung des Fragebogens hinsichtlich der modularen Anforderungen stattfand, bilden sich in der Konsequenz neben einer bildungswissenschaftlichen Ausrichtung auch Schwerpunkte ab, die sich in didaktischen und diagnostischen Kompetenzen sowie im Umgang mit Heterogenität zeigen. In dem Beitrag wird ein neu zusammengestelltes Erhebungsinstrument vorgestellt. Dies meint konkret, dass Entscheidungen für die Verwendung von bewährten (Sub-)Skalen offengelegt wer-den; entsprechend werden die modularen wie theoriegeleiteten Argumente für einzelne (Sub-)Skalen innerhalb der Erläuterung der einzelnen Kompetenzfacetten im Detail aufgeführt.

Single-channel electronic readout of a multipixel superconducting nanowire single photon detector - Tiedau, Johannes; Schapeler, Timon; Anant, Vikas; Fedder, Helmut; Silberhorn, Christine; Bartley, Tim (Optics Express)
We present a time-over-threshold readout technique to count the number of activated pixels from an array of superconducting nanowire single photon detectors (SNSPDs). This technique places no additional heatload on the cryostat, and retains the intrinsic count rate of the time-tagger. We demonstrate proof-of-principle operation with respect to a four-pixel device. Furthermore, we show that, given some permissible error threshold, the number of pixels that can be reliably read out scales linearly with the intrinsic signal-to-noise ratio of the individual pixel response.
Keywords: Atomic and Molecular Physics; and Optics

»Gestaltungsmittel« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

»Anspielung« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

»Briefsorte« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

»Gestalt« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

»Bricolage« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

A General Test for the Linear Structure of Covariance Matrices of Gaussian Populations - Xiao, Yu-Hang; Ramírez, David; Schreier, Peter J (Proc. IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Analoge Klangsynthese zur Vermittlung von Grundkenntnissen der Signalverarbeitung an Studierende nicht-technischer Fachrichtungen - Krumme, Matthias; Webersen, Manuel; Claes, Leander; Webersen, Yvonne (Fortschritte der Akustik - DAGA 2020)

Als ob... Was unterscheidet die Lernorte Schule und Gemeinde? - Schroeter-Wittke, Harald („Weil man halt ja nebenbei, so etwas gelernt hat...“ Lernortspezifische Jugendtheologie in Schule und Gemeinde.)

Völkerrecht und Völkerbund. Reinold von Thaddens juristische Dissertation von 1920 - Schroeter-Wittke, Harald (Staat - Religion - Recht. Festschrift für Gerhard Robbers zum 70. Geburtstag)

Siegfried Hermle / Dagmar Pöpping (Hgg.), Zwischen Verklärung und Verurteilung. Phasen der Rezeption des evangelischen Widerstandes gegen den Nationalsozialismus nach 1945 (AKZ B 67), Göttingen 2017 - Schroeter-Wittke, Harald (Jahrbuch für Westfälische Kirchengeschichte)

Thorsten Moos: Krankheitserfahrung und Religion. Tübingen 2017 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Die Himmel erzählen. Gottesdienstentwurf Reformationstag mit Beethoven (Mt 10,26b-33) - Schroeter-Wittke, Harald (Reformation mit Beethoven feiern 31. Oktober 2020. Evangelischer Bund Rheinland Düsseldorf)

Florian Dinger: Religion inszenieren. Ansätze und Perspektiven performativer Religionsdidaktik, Tübingen 2018 - Schroeter-Wittke, Harald (Loccumer Pelikan)

Wittgenstein - Weihnachten - Beethoven. Jazzrausch Bigband lässt alle Welt tanzen - Schroeter-Wittke, Harald (Praktische Theologie)

1. Sonntag nach Weihnachten 27.12.2020. Lukas 2,(22-24)25-38(39-40): Missionarische Spiritualität - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien III/1)

Am seidenen Faden - Liminalität im Kontext von Vergänglichkeit in Moden, Kleidung und Textil - Haller, Melanie; Helmers, Traute; Mallon (Hg.), Stefanie (Der Tod und das Ding. Textile Materialitäten im Kontext von Vergänglichkeit, Münster 2020, S. 379-400)

Körper Kleid Bewegung – Zum Verhältnis von Kleidern und Bewegungen am Beispiel vom Sportmoden - Haller, Melanie (In: textil. Wissenschaft, Forschung, Bildung 2/2020, S. 6-10.)